Impact of Tourism on Social Economic Development of Kabale Municipality Kabale District. - Twesiime, Robert (Kabale University, 2024)
The study was about assessing the contribution of tourism to the socio-economic development of the Kabale District. The study was guided by three objectives which were: to examine the Contributions of tourism to economic development in Kabale Municipality, Kabale District, to investigate the impacts of tourism towards economic development in Kabale District, to examine possible constraints to tourism development in Kabale Municipality, Kabale District. A targeted population was fifty-six (56) respondents who were considered for the study. These included senior staff, Head Guide, Manager, Tourists, Community members Local government officials. Both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included surveys, observations, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. According to the findings, 100% of the respondents agreed that there were several contributions of tourism to economic development in Kabale municipality, Kabale district included: Boosting scale industry revenues, Boosting revenue of the economy, developing infrastructures, a sense of cultural exchange between foreigners and citizens, job opportunities, source of foreign exchange earnings, tourism are often regarded as a tool in rural development. The study revealed the impacts of tourism on economic development in Kabale Municipality, Kabale Municipality, and Kabale District and these included tourism can encourage the displacement of locals, tourism can leave a large carbon footprint, a large number of moving visitors into an area push up the price of goods and services, decline in traditional employment which happens when workers move from industries such as farming. From objective three, the study indicated the relationship between tourism and social Economic Development, through the provision of small or micro enterprises for certain citizens, through infrastructure to support the tourist market or trade including factors like good airports, security, hotels and roads, tourism can create employment opportunities for local communities, tourism can contribute to the overall economic growth of a region or country by generating income through expenditures on accommodation, food, transportation, and entertainment, tourism facilitates cultural exchange between tourists and locals, promoting mutual understanding and appreciation, tourism can contribute to government revenue through taxes, fees, and permits, tourism can help diversify the economy of a destination, reducing dependence on a single industry.